The Impact of Pictograph-Based Education on Knowledge, Attitude, Self-Care, Fasting Blood Glucose and HbA1c Levels in Type 2 Diabetic Patients in Kerman - Fatemeh Nazari Robati; Narges Khanjani; Mohammad Reza Mahmoodi; Mohammad Mehdi Fadakar (Iranian Association of Health Education and Health Promotion, 2016)
Background and objective: Education can play an important role in the management of chronic diseases such as diabetes. This study was conducted to determine the impact of pictograph-based education on knowledge, attitude, self-care, fasting blood glucose and HbA1c among patients with type 2 diabetes. Materials and methods: This study was a randomized controlled trial (RCT) on 100 patients with type 2 diabetes referred to diabetes clinics in Kerman city. The participants were randomly divided into intervention and control groups with 50 patients in each group. In the intervention group, pictograph-based training was presented in the form of slides and posters along with lectures, but in the control group lectures without pictographs was presented. The data were collected and analyzed using chi-square tests, independent t-test, paired t-test Wilcoxon and Mann-Whitney U through SPSS16. Results: The mean score of total self-care significantly increased in the intervention group (p < 0.0001). The self-care components of foot care and blood glucose monitoring significantly improved in the intervention group, too. Fasting glucose and HbA1c decreased in both groups and knowledge in both groups improved after the intervention, but attitude only increased in the intervention group. Conclusion: Considering the significant role of pictographs in learning health instructions, it seems that education using pictographs can promote self-care behaviors among diabetic patients who are mainly old and/or with low literacy. Paper Type: Research Article.